Neuromuscular timing modification in responses to increased speed and proportional resistance while pushing a sled in young adults - Martin G. Rosario (Asociación Española de Ciencias del Deporte, 2020)
Introduction: The XPO Sled Trainer used in this research is a novel device that provides low rolling resistance at low speeds with an instant and automatic equivalent increment in resistance with increased speed. Purpose: To examine the impact of using the XPO Trainer on neuromuscular activation time at low and high speeds in young, seemingly healthy adults. Materials and Methods: This study consisted of 36 healthy adults (age: 24.6±3.9 years). Each participant wore surface electromyography (EMG) electrodes on their dominant leg over the anterior tibialis and gastrocnemius (GA). The four tasks examined in this work were, walk, run, walk pushing (WP) and run pushing (RP). Participants were asked to walk on their self-selected speed. To execute the tasks, participants walked and ran a distance of 40 feet both with and without the XPO Trainer sled. Subjects completed a total of 3 trials per task (total of 12) with one-minute breaks between tasks to reduce fatigue. Results: Neuromuscular time for activation was significantly modified while pushing the sled in both self-selected speeds, particularly in GA muscle. WP and RP exhibited an inverted relationship in neuromuscular timing patterns. Conclusion/Clinical Relevance: We suggest using the sled while walking to provoke endurance and running to work on strengthening of lower leg musculature. The sled proved to be a useful adjunct tool for neuromuscular training in different alterations of the lower limb muscles, especially the extensor musculature.